Linking short- to medium-term beach dune dynamics to local features under wave and wind actions: a northern portuguese case study - Bio, Ana (2022)
Many coasts suffer from prevailing erosion, with them being particularly vulnerable to predicted climate change impacts, threatening coastal ecosystems, their services, infrastructures and populations. Understanding coastal morpho-sedimentary dynamics is thus essential for coastal management. However, coastal vulnerability may differ locally, depending on exposure/protection and local geological and morpho-hydrodynamical features, suggesting that a local approach to erosion risk assessment is needed to identify and understand local patterns. Digital elevation models of a 14 km long coastal stretch in northern Portugal that were extracted from aerial surveys obtained between November 2008 and February 2019 were analysed to quantify changes in shoreline position and sediment budgets, both for the whole study area and for distinct beach segments. The observed dynamics were subsequently analysed by considering prevailing wave and wind intensities and directions. Overall and during the decade analysed, the beach–dune system of the studied stretch slightly increased in volume (0.6%), although the shoreline retreated (by 1.6 m on average). Temporal variability in coastal dynamics was observed at all of the temporal scales considered—from seasons to 5-year periods—with them being related to variability in ocean and wind patterns. There was a trend from accretional to erosional conditions, with the first 5-year period showing a mean increase in the beach–dune system’s volume of 0.6% and a mean shoreline progradation of 1.5 m, followed by 5-years with 0.0% volume change and 3.1 m shoreline retreat. Locally, the dynamics were very variable, with shoreline dynamics ranging from 24.0 m regression to 51.5 m progradation, and sediment budgets from 213.8 m3 loss to 417.0 m3 gain, per segment and for the decade. Stretches with relatively stable morphologies and others with erosional or accretional trends were found, depending on the beach type, shoreline orientation and the presence of defence structures. Rocky beaches were the least dynamic and sandy beaches the most dynamic, with mean shoreline position changes of 0.0 m and −3.4 m, respectively, and mean sediment budgets of −1.1 m3 and −2.9 m3 per linear meter of coastline, respectively, for the studied decade. The observed dynamics showed how local conditions interacted with meteo-ocean conditions in shaping local morpho-sedimentary dynamics, stressing the importance of a local approach to coastal erosion monitoring and risk assessment.